The Colorado Plateau VI : Science and Management at the Landscape Scale - Huenneke, Laura. F.; Van Riper, Charles, III, 1946-; Hays-Gilpin, Kelley A., 1960- (Book collections on Project MUSE., 2015)
"With a plethora of updates and insights into land conservation and management questions on the Colorado Plateau, The Colorado Plateau VI shows how new technologies for monitoring, spatial analysis, restoration, and collaboration improve our understanding, management, and conservation of outcomes at the appropriate landscape scale for the Colorado Plateau"--Provided by publisher.